Pengendalian Kualitas Kain Corak 0818 Pada Mesin Water Jet Loom Type Tsudakoma Dengan Menggunakan Metode Statistical Quality Control - Pravitasari, Filly; Nurherawati, Feny (Universitas Pahlawan Tuanku Tambusai, 2025)
PT X is a textile company in the weaving sector, producing fabrics with various patterns. Quality control plays an important role in the production process, production results with zero rejects are the target for every company. In the production process for 28 days (4 weeks) the total number of fabric defect points was 750 points, of which 285 points had snarling defects that appeared on the surface of the fabric in the form of small curves with a length of 1-4 mm. The snarling was caused by loose weft yarn and formed a twist, so that when it was pressed the yarn was carried into the fabric and the surface of the fabric looked rough. Based on the results of the analysis of the implementation of quality control, the fabric was still not under control, on the C control chart where there were 3 points outside the upper control (Upper Control Limit) and one point outside the lower control limit (Lower Control Limit). The cause and effect diagram shows several factors that cause snarling defects, namely humans, machines, methods and materials. The use and handling of the catch rope yarn must be considered so as not to block the weft yarn when sliding. Keywords: quality control, water jet loom, snarling